The Role of Asta Brata Leadership on MSME Performance During Pandemic, Financial Literacy Moderating - Putu Atim Purwaningrat; Ni Ketut Muliati; Luh Nik Oktarini (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
This study observes the leadership role of Asta Brata which is one of the local wisdoms in Bali towards improving the performance of MSMEs during pandemic. Some researchers usually use leadership style variables that are adopted from outside, so there is a need for reinterpretation and adaptation to local culture. This study also uses financial literacy as moderation. This study aims to determine the influence of Asta Brata's leadership on the performance of MSMEs in Badung Regency during the pandemic with Financial Literacy as moderation. The survey was conducted on 100 people MSME in Badung Regency. The data were collected through online form. The validity and reliability had been met. Data analysis was carried out by partial least square in structural equation model approach (SEM-PLS). The results showed that Asta Brata's Leadership positive and significant effect on MSME performance. Financial Literacy has a positive and significant effect on the performance of MSMEs. Financial Literacy is able to moderate the relationship between Asta Brata Leadership and the Performance of MSMEs in Badung Regency during the Pandemic.